Advances in Physiological Cardiac Stimulation - Galli Reis, Gustavo; Di Leoni Ferrari, Andres; Chiari Cabral, Gustavo; Ferreira Gazzoni, Guilherme; Manuel Ley, Luis; Feltrin Willes, Jessica Caroline; Costa Ferreira, Flavio Vinicius; Orlandini Lodi, Laura (JOURNAL OF CARDIAC ARRHYTHMIAS, 2021)
Advances in cardiac stimulation demonstrate that bradyarrhythmia treatments go beyond heart rate control. The concern with the ventricular stimulation site and, consequently, with the maintenance of intraventricular synchrony has become routine in most services. Techniques of physiological cardiac stimulation, such as stimulation of the bundle of His and the left branch, have been improved. Despite the indisputable benefits of these therapeutic modalities, there are technical difficulties that limit systematic use. In this sense, to make physiological cardiac stimulation more practical and reproducible, the concept of parahissian stimulation was expanded and studied. The technique, simpler and reproducible, contemplates a conventional approach of the right ventricle. The big difference is the use of QRS spatial variance analysis technology (Synchromax®, Exo S.A., Argentina) to confirm the maintenance of ventricular synchrony according to the implanted site.